Proceedings of the 14th ACM / IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2020
DOI: 10.1145/3382494.3422169
|View full text |Cite
|
Sign up to set email alerts
|

How long do Junior Developers take to Remove Technical Debt Items?

Abstract: Background. Software engineering is one of the engineering fields with the highest inflow of junior engineers. Tools that utilize source code analysis to provide feedback on internal software quality, i.e. Technical Debt (TD), are valuable to junior developers who can learn and improve their coding skills with minimal consultations with senior colleagues. Objective. We aim at understating which SonarQube TD items junior developers prioritize during the refactoring and how long they take to refactor them. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(32 reference statements)
0
5
0
2
Order By: Relevance
“…Lenarduzzi et al investigaron un caso de estudio con 185 desarrolladores junior en dos países, que desarrollaron 23 aplicaciones en diferentes lenguajes de programación y arquitectura. Determinaron el alto nivel de aprecio de SonarQube para la reducción de limpieza de código, nunca gastando más del 50% del tiempo estimado [14].…”
Section: Trabajos Relacionadosunclassified
See 1 more Smart Citation
“…Lenarduzzi et al investigaron un caso de estudio con 185 desarrolladores junior en dos países, que desarrollaron 23 aplicaciones en diferentes lenguajes de programación y arquitectura. Determinaron el alto nivel de aprecio de SonarQube para la reducción de limpieza de código, nunca gastando más del 50% del tiempo estimado [14].…”
Section: Trabajos Relacionadosunclassified
“…Para la evaluación de olores de código, se utilizó SonarQube como herramienta automatizada, logrando disminuir el valor de 207 a 22. Respecto a la deuda técnica se redujo de 2.3% (2 días 1 hora) a 1.8% (3h 4min), valores significativos, en correspondencia a lo afirmado por Lenarduzzi et al[14].Se redujo la densidad del código repetido de 7% a 0%, resultado que debiera relacionarse con la densidad de complejidad ciclomática, que en el caso estudiado solo se redujo de 184 a 176, manteniendo un nivel muy alto de riesgo para la capacidad de modificación[20].En la evaluación de fiabilidad con SonarQube se pasó de nivel de confiabilidad de C a A, valor significativo que guarda coherencia con lo mencionado por Marcilio et al que mencionaron que las organizaciones con proyectos de software que utilizaron SonarQube resolvieron los problemas en los sistemas en un 13%[15].20 th LACCEI International Multi-Conference for Engineering, Education, and Technology: "Education, Research and Leadership in Post-pandemic Engineering: Resilient, Inclusive and Sustainable Actions", Hybrid Event, Boca Raton, Florida-USA, July 18 -22, 2022.…”
unclassified
“…However, comparing the effort needed by developers to repay Technical Debt with the one proposed by SonarQube, remediation time is generally overestimated by the tool compared to the actual time for patching Technical Debt items. The most accurate estimations are related to Code Smells, while the least accurate to Bugs [11], [40], [41].…”
Section: Related Workmentioning
confidence: 99%
“…They found that the estimations were only correct for 2 projects, for 9 projects they were overestimated. Lenarduzzi et al [40] investigated (among others) how long it takes for junior developers to refactor technical debt items detected by SonarQube. They found that the time estimated by SonarQube was always at least 2 times higher than the actual fixing time, in some cases 20 times higher.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, the reported data are frequently overestimated ( [52]). In case of junior developers it could even be up to 2 -20 times ( [40]). The fault proneness of the found issues (how likely they would be to lead to bugs) might also be unclear ( [39], [44]).…”
Section: Introductionmentioning
confidence: 99%